Кинематографический образ учителя как средообразующий фактор - Куконков, И.П. (My University, 2013)
During the formation of a unified state policy in the field of education, it is a vision of the image of a teacher as a conductor of state ideology. At the same time, through the formation of teachers ki- noobraz intellectuals, as the voice of public opinion, is able to demonstrate to the state and educational community expectations, existing in society, in relation to teacher.